Coalescence-induced jumping of immersed and suspended droplets onmicrostructured substrates - Farokhirad, Samaneh; Shad, Mahmood Mohammadi; Lee, Taehun (European Journal of Computational Mechanics, 2019)
The coalescence-induced jumping of liquid droplets on superhydrophobic structured substrates is investigated numerically using a three-dimensional multiphase lattice Boltzmann method. The numerical experiments on evolution of droplets during jumping process show higher jumping velocity and height from superhydrophobic substrates structured with a periodic array of square pillars, than flat superhydrophobic substrateswith an equilibrium contact angle of 180◦. The results further reveal a strong effect of pillars on the vertical jumping velocity and the final quasiequilibrium height of the merged droplet as a function of air and liquid viscosity, as well as air inertia. As for substrate wettability, it is found that, compared to the flat superhydrophobic substrate, the critical contact angle where the merged droplet jumps away from substrate is reduced for pillared substrate and is about 120◦. It is also observed that the droplet initial placement on a substrate with a square array of pillars has an important effect on the spontaneous jumping of the coalesced droplet, and a Wenzel–Cassie wetting transition upon coalescence is observed for droplets that are initially immersed within the pillars.